Raising Legal Awareness in MSME Trade: Protecting and Registering Trademarks - Siagian, Putri Rumondang; Desiandri, Yati Sharfina; Saidin, Saidin; Shauqi, Saddam; Wau, Hilbertus Sumplisius M.; Azwar, T. Keizerina Devi (Nagari Law Review, 2025)
Micro, Small, and Medium Enterprises (MSMEs) as small-scale industries tend to ignore the importance of intellectual property protection, particularly evident in the minimal registration of MSME trademarks with the Directorate General of Intellectual Property. Although the World Intellectual Property Rights (WIPO) recognizes the potential of MSMEs to drive product innovation and creativity, MSME awareness of the use of Intellectual Property Rights remains low. This study uses a normative legal research method, focusing on the study of legal provisions related to MSME trademark registration and protection. A descriptive analytical approach is used to identify and resolve existing legal issues, with reference to relevant laws and regulations. Trademark registration is considered the basis for rejecting similar trademarks filed by other parties for similar goods or services. The "first to file" principle applies in Indonesia, which grants exclusive rights to the first registrant for 10 years. Efforts to increase MSME legal awareness of the importance of trademarks, particularly through registration, are crucial. Legal counseling can be an effective means to increase public understanding, by emphasizing the legal protection and legal certainty provided by trademark registration. The importance of legal counseling as a strategy to increase legal awareness among MSMEs in registering their trademarks needs to be considered. This awareness can ensure that MSMEs understand the importance of brands to their businesses and can manage them legally to maintain their protection. This study recommends the need for further provision and understanding through legal counseling to ensure better legal awareness among MSMEs.